(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Theapsorbtion capacity of the large bowel was studied by us amoung 6 dogs(24 experiments) before and after the resection of the stomach according to Hofmeister-Finsterra.The study was conducted 3.7.15.30 days after the reseption of the stomach using the method of the biological injection.The receotion of the Stomach causes the terminal displacement of food absorption in the intestine especially after the resection of the stomsch according to Hofmeister-Finsterracjmes out a new function of the large bowel to absorb fat that is not characteristic for lymphatic vessels which testifies about the complementary-adaptive abilities of lymphatic vessels.